2022
DOI: 10.3390/cells11050918
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Optical Motion Tracking Allows Monitoring of Respiratory Dynamics in Dystrophin-Deficient Mice

Abstract: Duchenne muscular dystrophy (DMD) is the most common x-chromosomal inherited dystrophinopathy which leads to progressive muscle weakness and a premature death due to cardiorespiratory dysfunction. The mdx mouse lacks functional dystrophin protein and has a comparatively human-like diaphragm phenotype. To date, diaphragm function can only be inadequately mapped in preclinical studies and a simple reliable translatable method of tracking the severity of the disease still lacks. We aimed to establish a sensitive,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…In comparison, we demonstrated that with a rather simple approach of cinematic planar phase contrast imaging, we derived significant differences in lung function parameters that allowed discriminating between asthmatic and healthy mice. Even more importantly, we were able to demonstrate that with a temporal resolution of 100 fps, the phase of elastic recoil of the lung and the dampening effect of the diaphragm could reliably be detected, a characteristic feature of asthmatic mice (29), that so far we were only able to detect with optical cameras at the same high frame rate of 100 Hz (30). The concept of extraction breathing motion by analyzing the average x-ray transmission in a region of interest typically on top of the lung-diaphragm interface is a well-known approach introduced for instance by Ford and Bartling (31,32).…”
Section: Discussionmentioning
confidence: 95%
“…In comparison, we demonstrated that with a rather simple approach of cinematic planar phase contrast imaging, we derived significant differences in lung function parameters that allowed discriminating between asthmatic and healthy mice. Even more importantly, we were able to demonstrate that with a temporal resolution of 100 fps, the phase of elastic recoil of the lung and the dampening effect of the diaphragm could reliably be detected, a characteristic feature of asthmatic mice (29), that so far we were only able to detect with optical cameras at the same high frame rate of 100 Hz (30). The concept of extraction breathing motion by analyzing the average x-ray transmission in a region of interest typically on top of the lung-diaphragm interface is a well-known approach introduced for instance by Ford and Bartling (31,32).…”
Section: Discussionmentioning
confidence: 95%
“…The k-value as a constant of a Gaussian function fitted to the expiratory phase is predominately measuring the effect of elastic recoil of the lung in combination with an later onset of a dampening effect of the diaphragm 21 and is therefore especially sensitive for characterizing the mdx mice known for fibrotization of the diaphragm 22 . Clinically the expiratory time constant (RCexp) is a known measure that combines effects of changes in compliance and resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Search for finding a simpler way than WBP and XLF to monitor respiratory dynamics, resulted in introduction of an optical technique by Svetlove et al called optical respiratory dynamics tracking (ORDT) ( Svetlove et al, 2022 ). This technique is especially useful for tracking diaphragm function of mice with neuromuscular diseases such as Duchenne muscular dystrophy (DMD).…”
Section: The Role Of Pulmonary Function Tests In Preclinical Lung Res...mentioning
confidence: 99%
“…Furthermore, unlike XLF technique, ORDT was also able to show the differences between fast and slow expiratory phases in mdx mice, while healthy controls had almost the same fast and slow phases. Compared to the alternative methods for longitudinal assessment of diaphragm function in mice, e. i. WBP and XLF, ORTD is easier to perform, completely non-invasive (no ionizing radiation), cheaper, and can be performed by commonly available tools and equipment ( Svetlove et al, 2022 ). Furthermore, since this optical technique directly assess the dynamics of the body surface, it has a greater potential in detecting abnormal breathing patterns.…”
Section: The Role Of Pulmonary Function Tests In Preclinical Lung Res...mentioning
confidence: 99%